Determination methods of food fibers characteristics in milk mixtures with the modified fat composition - Grek, Olena; Tymchuk, Alla; Tsygankov, Sergii; Savchenko, Alexander; Ovsiienko, Kira; Ochkolyas, Olena (My University, 2019)
The main methods of determining the technological parameters of dietary fiber in milk mixtures of modified fat composition are presented in the article. Methods for investigating the ability of food fibers to moisture and fat absorption are proposed. The values ​​characterizing the swelling parameters of the herbal ingredients in the experimental mixtures were obtained. The effectiveness of the IR spectroscopy method for the identification and comparison of moisture bond forms in mixtures of food fibers with water and oil was confirmed. The parameters of thermal stability and degree of leakage of liquid fat for mixtures of modified fat composition with maximum butter oil replacement by 25% of oil were obtained. The results of the studies indicate that there are objective possibilities for the effective use of Vicetal dietary fiber, to stabilize the structure and to prevent the appearance of defects in the consistency of products with modified fat composition.
Keywords: молочні суміші з модифіковани жировим складом; харчові волокна; жироутримування; milk mixtures with the modified fat composition; food fibers; fat-retaining; кафедра технології молока і молочних продуктів